Engaging with the More-Than-Human and Decolonial Turns in the Land of Shinto Cosmologies: "Negative" Comparative Education in Practice. (March 2020) - Takayama, Keita
Purpose: In this explorative, self-reflective article, I attempt to extend the methodological discussion of a "negative" approach to comparative education that I have recently articulated elsewhere. Here, I demonstrate how I attempted to put in practice negative comparative education by drawing on my experience at the Shanghai workshop, Beyond the Western Horizon in Educational Research, organized by Iveta Silova, Jeremy Rappleye, and Yun You at the East China Normal University. Design/Approach/Methods: I conceive my participation in the Shanghai workshop as a disruptive moment wherein my previous forms of knowing and being were challenged. More specifically, I discuss how my attempt to situate the ecofeminist and decolonial literature, the two of the three main bodies of literature introduced through the workshop, within the context of Japanese education triggered me to reconsider the role of Shinto in Japanese education and question my own firm identification with the liberal–left politics within Japan. Findings: I reflect upon how the initial sense of discomfort and the remaining sense of ambivalence took me on a journey of unlearning and relearning about the limits of my knowing, my own political subjectivities, and the place of Shinto cosmologies in Japanese education. Originality/Value: I conclude the discussion with a few provisional thoughts that point us to an approach to comparative education that makes our research "a matter of concern" across multiple linguistically bounded, national and regional scholarly communities.